Development of in vitro embryo production device with sperm sorting function - Tsubasa TAKAHASHI; Hiroko NAKAMURA; Hiroshi KIMURA (Nihon Kikai Gakkai ronbunshu, 2017)
Nowadays, in vitro fertilization (IVF) of mammalian embryos is an essential technique in the reproductive technology and other related life science fields. However, the fertility rate by this technique is still less than 25%. Therefore, a novel in vitro fertilization method which obtains high fertility rate has been highly desired to the reproductive technology. In this study, we proposed and developed an in vitro embryo production device which allows three steps of sperm selection, fertilization and culture on a microdevice. To realize this concept, we integrated the sperm sorting function combining with swim-up and swim-down methods onto the device. To evaluate the device functions, sperm sorting experiment, in vitro fertilization experiment, and embryo culture experiment have been carried out. As results, we concluded that the device has ability to produce high quality embryos by integrating the sperm sorting function. This concept will open and enhance the management of in vitro fertilized embryos for assisted reproductive technology, livestock breeding, and fundamental stage research by further development.